Self-gripping mesh versus polypropylene mesh in ventral hernia repair: an observational study - Kumar, V. Om; Subbiah, Venkatesh (International Surgery Journal, 2020)
Background: To compare clinical outcomes following sutureless Parietex ProGrip™ mesh in ventral hernia repair to traditional lightweight polypropylene mesh secured with sutures. Methods: This was a study conducted at the Department of General Surgery in Velammal medical college from August 2019 to February 2020. This prospective observational study involved, 60 patients, 30 each undergoing ventral hernia repair with polypropylene mesh with suture fixation and Parietex ProGrip™ precut mesh (P group) without fixation. The primary outcome measure was postoperative pain using the visual analog scale were assessed prior to surgery and up to 3 months postoperatively (VAS, 0-150 mm); other outcomes (duration of surgery, wound infection and recurrence of hernia) were assessed up to 3 months postoperatively. Results: Compared to baseline (preoperative), pain score below four on the visual analogue scale was higher in the test group at discharge (76.7%) and 24 hours (96.7%), while the pain was more in the study group at discharge (43.3%) and seven days (70%). The difference between groups was significant at both time points. In the test group, patients without fixation suffered less pain compared to those with single-suture fixation (48 hours: 100% versus 86.6%, p=0.038; 3 months: 100% versus 100%, p≤0.001). Surgery duration was significantly shorter in the test group (<60 minutes) (66.7% versus 40%; p<0.038). No recurrence was observed at three months in both groups. Conclusions: A self-gripping mesh for ventral hernia repair may result in less pain in the early postoperative phase. Recurrence rates reduce as well as the patient’s quality of life improves.